Teaching Writing of Argumentative Essay Using Collaborative Writing Technique Viewed from Studentsâ Creativity: an Experimental - Ghufron, M. Ali; Hawa, Masnuatul (Proceeding of International Conference on Teacher Training and Education, 2016)
The use of small group and pair work in classrooms, particularly in second language (L2) classrooms, rests onstrong theoretical and pedagogical bases. This research was aimed at finding out: (1) whether or notCollaborative Writing Technique is more effective than Direct Instruction in teaching writing ofargumentative essay; (2) whether the students who have high creativity have better writing ability than thosewho have low creativity; and (3) whether there is an interaction between teaching techniques and creativity in teaching writing. This experimental research was carried out in IKIP PGRI Bojonegoro in the academic year of 2014/2015 from March 2015 to June 2015. The population was the fourth semester students of English Education Department in the academic year of 2014/2015, and the number of population was 126 students who were divided into three classes. The samples, which were selected by using cluster random sampling, were IIB as the experimental group and IIA as the control group. Each group consists of 42 students. Theexperimental group was treated by using Collaborative Writing Technique, while the control group wastreated by using Direct Instruction. The data analysis shows the following findings: (1) Collaborative WritingTechnique is more effective than Direct Instruction in teaching writing; (2) students with high creativity havebetter writing ability than those having low creativity; and (3) there is an interaction between teachingtechniques and creativity in teaching writing.